METHODOLOGY FOR THE CALCULATION OF EMISSIONS FOR NON-STATIONARY TRANSPORT FLOW - E. V. Parsaev; P. N. Malyugin; I. A. Teterina (Вестник СибАДИ, 2018)
Introduction. Two methods among five in regulatory documents of the Russian Federation can be interested for assessing the quality of traffic management by environmental indicators. Only such methods take into account the parameters of the traffic flow that affect the volume of emissions. The parameter influencing the results of calculations in both methods is an average motion speed. Moreover, there are areas on urban highways, where traffic moves unevenly (braking, dispersal, stopping). Therefore, such factor entails an increase in the volume of emissions from vehicles. At the same time, this uneven movement is largely due to the existing organization of traffic (TO) on certain elements of the street-road network (SRN). Accordingly, the method for calculating pollutant emissions to assess the quality of TO, which take into account the unevenness of traffic flow, should be developed.Materials and methods. The paper proposes to take into account the average speed of traffic in those parts, where the traffic flow moves stationary, and on the elements of the main traffic line, where the traffic flow is non-stationary, and to take into account additional emissions. Moreover, the additional emission from the traffic flow should be considered separately in the following cases: if the cars stop (there are deceleration modes, idling and acceleration) and in the situation, when cars decrease their speed (slowdown and acceleration).Results. As a result, the difference between calculations of carbon monoxide emissions by the proposed method and by the GOST methodology is 57%, and for emissions of nitrogen oxides is 94%.Discussion and conclusion. The proposed methodology allows accurately assessing the quality of the TO on the section of the urban highway and its individual elements on environmental indicators. In addition, the proposed methodology would allow carrying out calculations for the evaluation of road traffic projects and activities, which aim to reduce the harmful impact of traffic on the environment of the highway areas.